PERAN VITAL BASYARNAS DALAM PENYELESAIAN SENGKETA BISNIS SYARIAH - Masyithah syita (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2021)
The emergence of Islamic financial institutions in Indonesia is good progress for the Muslim community. however, the demands of the system and its management also arise with its increasing development. Moreover, solving problems also suppresses the existence of institutions that can handle them. Arbitration that has been carried out by the Prophet, khulafaurrasyidin even in the dynasties that followed is an out of court dispute resolution that can be an option for businessmen. On the initiative of the MUI, by going through several processes, the National Sharia Arbitration Board was formed to resolve disputes between sharia business parties.